The Effect of Architecture Style on The Housing Thermal Condition in Humid Tropical Area - Feriza Nadiar; I Gusti Ngurah Antaryama; Ima Defiana (Institut Teknologi Sepuluh Nopember, 2017)
Modern minimalist, Mediterranean and Modern tropical style are commonly found architecture styles in residences in Surabaya in the past decade. However, it is ironic that most of the styles are imported products which have different response level towards the local climate due to the fact that they are not designed for humid tropical areas. Thus, the choice of style has become really important so that the building can respond well to climate. This research was conducted on three architecture styles with three variants of each in a residential area in East Surabaya. This paper evaluates thermal performances and the influence of envelope elements on the thermal conditions in each sample house and evaluates which style that is potentially applicable to the humid tropical climate by using simulation method with the assistance of ECOTECT software. The results show that the variant B of modern minimalist style has the best envelope performance. Overall, house envelope with the original design is not effective enough. Design modification with good and suitable elements for the B variant of the Modern minimalist and Mediterranean turn out to be resulting in a more effective in solving thermal problems.